S3 guidelines: Epicutaneous patch testing with contact allergens and drugs - Short version, Part 1 - Mahler, Vera; Weisshaar, Elke (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
Epicutaneous patch testing is the diagnostic standard for the detection of allergic contact dermatitis. The present guidelines are aimed at residents and board-certified physicians in the fields of dermatology and allergology as well as other medical specialties involved in establishing the indication for patch testing and its execution in patients with contact dermatitis and other forms of delayed-type hypersensitivity. The target audience also includes other health care providers and insurance funds. Based on a systematic literature search and a formal consensus process (S3), the guidelines were developed by dermatologists in collaboration with pediatricians, occupational medicine physicians, nursing staff as well as patient representatives. The systematic methodological approach and appraisal of evidence upon which the recommendations are based are outlined in a separate method report that also contains evidence tables. The guidelines address general aspects of patch testing as well as medicolegal issues. The recommendations given relate to topics such as the indication for patch testing, informed patient consent, as well as the choice of test substances, test chambers and test site, duration of exposure, reading times and interpretation of test reactions. Furthermore, recommendations are provided with respect to endogenous and exogenous factors, specific patient groups (children, pregnant women, immunosuppressed individuals) as well as possible risks and adverse events associated with patch testing using contact allergens. Note: This publication is part 1 of the short version of the S3 guidelines for “Epicutaneous patch testing using contact allergens and drugs” (registry no. 013 - 018; date: March 20, 2019; valid until December 31, 2021). Part 2 of the short version will be published in the next issue. The long version of these guidelines can be accessed at www.awmf.org. The method report is available as online publication (https://www.awmf.org/leitlinien/detail/ll/013-018.html) and contains the evidence tables in its appendix.